MENINGKATKAN KEAKTIFAN BELAJAR DENGAN PENDEKATAN PEMBELAJARAN BERDIFERENSIASI MENGGUNAKAN MODEL PEMBELAJARAN PROJECT BASED LEARNING - Habib Setiawana; Eddy Haryanto; Bunga Ayu Wulandari (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to improve students’ learning activeness in the IPAS subject through the implementation of a differentiated learning approach using the Project-Based Learning (PjBL) model in Grade V of SDN 126/VI Muara Jernih. The method employed was Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles with 24 students as research subjects. Data were collected through observation, interviews, documentation, and learning outcome tests, then analyzed using descriptive qualitative and quantitative methods. The results of the study indicate an increase in students’ learning activeness from 64% in Cycle I to 81.28% in Cycle II. Improvements occurred across all activity indicators, including visual, oral, listening, writing, and motor activities. The implementation of project-based differentiated learning was proven effective in creating participatory, meaningful, and student-centered learning.